Brain ventricular volume and cerebrospinal fluid biomarkers of Alzheimer’s disease - Ott, Brian R. (2010)
The frequent co-occurrence of Alzheimer disease (AD) pathology in patients with normal pressure hydrocephalus suggests a possible link between ventricular dilation and AD. If enlarging ventricles serve as a marker of faulty cerebrospinal fluid (CSF) clearance mechanisms, then a relationship may be demonstrable between increasing ventricular volume and decreasing levels of amyloid beta peptide (Aβ) in CSF in preclinical and early AD. CSF biomarker data (Aβ, tau, and phosphorylated tau) as well as direct measurements of whole brain and ventricular volumes were obtained from the Alzheimer's Disease Neuroimaging Initiative dataset. The ratio of ventricular volume to whole brain volume was derived as a secondary independent measure. Baseline data were used for the group analyses of 288 subjects classified as being either normal (n=87), having the syndrome of mild cognitive impairment (n=136), or mild AD (n=65). Linear regression models were derived for each biomarker as the dependent variable, using the MRI volume measures and age as independent variables. For controls, ventricular volume was negatively associated with CSF Aβ in APOE ε4 positive subjects. A different pattern was seen in AD subjects, in whom ventricular volume was negatively associated with tau, but not Aβ in ε4 positive subjects. Increased ventricular volume may be associated with decreased levels of CSF Aβ in preclinical AD. The basis for the apparent effect of APOE ε4 genotype on the relationship of ventricular volume to Aβ and tau levels is unknown, but could involve altered CSF-blood-brain barrier function during the course of disease.